Pelatihan Menyusun Laporan Cash flow Usaha Kecil bagi Warga Belajar Cerdas Mandiri Peureulak - Jamali; Wiriani, Erni; Jamil, Muhammad; Evawani, Cut (BA: Jurnal Pengabdian kepada Masyarakat, 2023)
The cash flow report is an important tool in managing business finances, because it provides information about cash inflows and outflows within a certain period. In this training, participants will learn the basic concepts of cash flow, including the meaning and importance of cash flow reports in making business decisions. They will study the various components of a cash flow statement, including cash flows from operating, investing and financing activities. In addition, participants will also learn how to use software or applications that can assist in preparing cash flow reports efficiently. This training will provide an understanding of how to use the tool and how to implement small business financial data into the software. This training is designed to allow participants to put what they learn into practice right away. They will be given training tasks to prepare cash flow reports based on real data from their own small businesses. This will help participants apply the knowledge and skills they have acquired in the training. After attending this training, Peureulak Mandiri Smart Learning residents will have a better understanding of cash flow reports and be able to prepare accurate cash flow reports for their small businesses. This will help them manage their business finances more effectively and make better decisions for their business growth.